Globalization and Pork Raising in Mexico: The Challenges of Integration to the World Market - del Carmen Hernánde, María; J. Maya, Carlos (The International Journal of Sociology of Agriculture and Food, 2021)
For many farm producers in the northwest from Mexico the participation in the international markets precedes the phenomenon of globalization; nevertheless, the opening of the Mexican market and the changes derived from the economic politics towards the field, are delineating new productive settings - so much so that a redefinition of the relations of production is required. Understanding the present state of activities of the sector in this zone of Mexico is fundamental to a consideration of the expansion of commerce as a greater strategy of economic politics in which the national priorities have been modified. Food production becomes the primary focus and goal, with internal consumption playing a secondary role. At the same time it has generated 'empty' institutional arrangements which have lead to uneven outcomes. This paper examines pig meat production in the state of Sonorous, and the insertion of farmers into the international marketplace.